Understanding and Diagnosing Antimicrobial Resistance on Social Media: A Yearlong Overview of Data and Analytics. Issue 2 (28th January 2019) - Andersen, Brittany; Hair, Lee; Groshek, Jacob; Krishna, Arunima; Walker, Dylan
ABSTRACT: To better understand user conversations revolving around antibiotics and antimicrobial resistance (AMR) on Twitter, we used an online data collection and analysis toolkit with full firehose access to collect corpuses of tweets with "antibiotic" and "antimicrobial resistance" keyword tracks. The date range included tweets from November 28, 2015, to November 25, 2016, for both datasets. This yearlong date range provides insight into how users have discussed antibiotics and AMR and identifies any spikes in activity during a particular time frame. Overall, we found that discussions about antibiotics and AMR predominantly occur in the United States and the United Kingdom, with roughly equal gender participation. These conversations are influenced by news sources, health professionals, and governmental health organizations. Users will often defer to retweet and recirculate content posted from these official sources and link to external articles instead of posting their own musings on the subjects. Our findings are important benchmarks in understanding the prevalence and reach of potential misinformation about antibiotics and AMR on Twitter.